The First-Person Authority of Children - Borgoni, Cristina; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This is an open-access book that examines how we respond to first-person authority, particularly that of infants and children. We respond to people$1 (Bs first-person authority when we give our interlocutor$1 (Bs communication of their mental states more significance in establishing their thoughts, desires, and feelings than if another person were to report those mental states for them. But what happens when our interlocutors are infants and children? Increasingly, practices of responsive childrearing ascribe first-person authority to very young children. Despite this tendency, philosophy seems to be one step behind. The accepted view is one in which first-person authority has its locus in linguistic expressions of one$1 (Bs self-knowledge. This is an over-intellectualized conception, however, that consequently tends to exclude children. By combining philosophical resources with empirical findings about the onset of human communication, play, and our nature as social beings, this text advances a non-intellectualized, anti-individualist, and non-adult-centered view of first-person authority. This is a view that both accommodates our daily experiences and provides material for advancing the philosophical debate around the phenomenon in an enriched and more inclusive way.s
Persons -- First Person Authority -- Authoritative Playful Minds -- Concluding Remarks.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Knowledge, Theory of; Developmental psychology; Philosophy of mind; Epistemology; Developmental Psychology; Philosophy of Mind